2000
DOI: 10.1182/blood.v96.4.1582.h8001582_1582_1584
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea-induced marked oscillations of platelet counts in patients with polycythemia vera

Abstract: Two prospectively studied patients with polycythemia vera (PV) whose platelet counts showed marked periodic fluctuation during treatment with hydroxyurea (HU) are reported. Cycle lengths in both were approximately 28 to 30 days. In one patient, the cyclic process was no longer evident when treatment with HU was withheld, and it reappeared on treatment rechallenge. Circulating thrombopoietin (TPO) levels fluctuated out of phase with the platelet count despite markedly reduced TPO-receptor (c-Mpl) expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 17 publications
2
26
1
Order By: Relevance
“…The population distribution of all significant periods of oscillation for platelet and leucocyte counts showed that the most prevalent periods across the cohort were 27 ± 1 d for platelets and 15 ± 1 d for leucocytes (Fig ). Less prevalent peaks were observed for platelets at 15 ± 1 d and 45 ± 1 d, and for leucocytes at 30 ± 1 d and 78 ± 1 d. Each of these periods noted within our cohort overlap with values previously described in the literature for both haematological lineages (Fortin & Mackey, ; Tefferi et al , ; Bennett & Grunwald, ; Steensma et al , ; Burthem & Chaudhry, ; Tauscher et al , ). At the cohort level, hydroxycarbamide appeared to have a consolidating effect upon the distribution of detectable periods for oscillating platelet‐ and leucocyte‐producing bone marrow populations, leading to fewer dominant periods while receiving the drug (Fig ).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The population distribution of all significant periods of oscillation for platelet and leucocyte counts showed that the most prevalent periods across the cohort were 27 ± 1 d for platelets and 15 ± 1 d for leucocytes (Fig ). Less prevalent peaks were observed for platelets at 15 ± 1 d and 45 ± 1 d, and for leucocytes at 30 ± 1 d and 78 ± 1 d. Each of these periods noted within our cohort overlap with values previously described in the literature for both haematological lineages (Fortin & Mackey, ; Tefferi et al , ; Bennett & Grunwald, ; Steensma et al , ; Burthem & Chaudhry, ; Tauscher et al , ). At the cohort level, hydroxycarbamide appeared to have a consolidating effect upon the distribution of detectable periods for oscillating platelet‐ and leucocyte‐producing bone marrow populations, leading to fewer dominant periods while receiving the drug (Fig ).…”
Section: Resultssupporting
confidence: 85%
“…Within the scope of hydroxycarbamide maintenance therapy in SCD, while the shifts between nadirs and zeniths in these patients' blood counts may appear precipitous in the short term, our data indicates that, in general, this pattern does not pose a danger of myelotoxicity to the patient, and recovery to normal ranges occurs in many cases without intervention. As noted in previous cases, it appears that stable and consistent hydroxycarbamide dosing leads to dampening of the oscillatory behaviour over time, while frequent dosage changes often lead to amplification of the oscillations and even more far ranging nadirs and zeniths (Kennedy, ; Tefferi et al , ; Bennett & Grunwald, ; Steensma et al , ; Tauscher et al , ). Importantly, our results indicate that oscillatory haematopoiesis is not a phenomenon limited to malignant or pre‐malignant haematological disorders, a finding that should prompt further investigation of its significance and prevalence in other patient populations receiving cell cycle‐specific inhibitors.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations